Associados à resistência a antimicrobianos em sedimentos após o colapso da barragem de fundão em Mariana, Minas Gerais - Amanda Aparecida Figueiredo Carvalho (2022)
The evolution and spread of antimicrobial resistance in recent years has become alarming, culminating in a threat to global health. In these circumstances, controlling the spread of antimicrobial resistance requires a multidisciplinary effort to understand the distribution of genetic markers associated with this property. In November 2015, the collapse of the Fundão dam, in Mariana, Minas Gerais, was declared the biggest environmental disaster in the mining sector in the world, due to the impacts related to the mineral tailings that reached the Rio Doce watershed (BHRD). This study aims to detect 16s rDNA, the integrase gene encoding subclass 1 (intl1) and 2 (intl2) integrons and the following antimicrobial resistance genes (ARGs): vanA, ermC, qnrB, sul1, sul2, tetM, blaKPC, blaNDM, blaNDM-1, blaSHV, blaTEM and blaVIM in two samplings, the first carried out in February and the second in July, both in 2019 in the Piranga and Santo Antônio River sub-basins located in the BHRD. The DNA of the samples was extracted and subjected to a quantitative chain polymerization reaction. The results showed that the mean values of relative abundance for intl1, qnrB, sul1, sul2 and blaTEM were higher in February 2019 in BHRD, as well as the prevalence of intl1, ermC, qnrB, sul1, sul2 and blaTEM in the same period. Furthermore, genes sul1, sul2 and qnrB showed the highest quantifications in number of gene copies per gram of sediment. Therefore, these AGRs, together with the intl1, can be dispersed more easily in sediments than others, especially in rainy periods, due to the high rainfall of this period in tropical climates. Another finding in this study was the higher prevalence, variety and quantity of genetic markers detected in the Piranga River sub-basin when compared to the Santo Antônio River sub-basin.